Political Participation of Novice Voters in the Implementation of Regional Head Elections - Djama, Sofyan; Mahmud, Ramli; Hamim, Udin (Dinasti Research, 2025)
This study aims to examine the forms of political participation among first-time voters during the 2024 simultaneous Regional Head Election in Bone Bolango Regency, with a focus on three main indicators: political campaigns, political discussion, and voting. The research employed a qualitative method with data collection techniques including observation, interviews, and documentation from various sources, such as the General Elections Commission (KPU), Election Supervisory Body (Bawaslu), the National Unity and Politics Agency (Kesbangpol), and the first-time voters themselves. The findings indicate that participation in political campaigns tends to be symbolic; most first-time voters take part due to social influences and peer encouragement rather than a deep understanding of the candidates’ visions and missions. Regarding political discussions, only a small proportion of first-time voters actively engage in conversations about political issues, while the majority remain passive, citing a lack of understanding or interest in politics. In terms of voting, decisions are heavily influenced by family, particularly fathers, who serve as key references in political choices. In addition to participation patterns, this study identifies three primary factors that determine the level of first-time voter engagement: (1) social media, as the main source of political information and digital discussion; (2) political party identification, which shapes loyalty and preference; and (3) family ties, which serve as the dominant influence in political decision-making. These three factors interact to form a distinctive pattern of political participation among first-time voters in Bone Bolango Regency.